An interactive location system for smart places - Coitos, B. (2020)
In this work, we describe a prototype that was developed as an inte- grated system that provides relevant information in an interactive way when in- side of complex buildings, such as museums, hospitals, shopping malls, amongst others. To accomplish this, the system uses an Indoor Location and Tracking System taking advantage of BLE devices and Bluetooth capabilities of mobile devices. This prototype is also composed of an open-source Content Management System (based on Drupal 8), that allows the system operators to upload and manage the information provided to the mobile users, with the pos- sibility of uploading files extracted from BIM tools. The resulting system is af- fordable for Smart Places while being comfortable and interactive for the users.